2008
DOI: 10.1039/b802931h
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing cell mechanics in hematologic diseases with microfluidic biophysical flow cytometry

Abstract: Pathological processes in hematologic diseases originate at the single-cell level, often making measurements on individual cells more clinically relevant than population averages from bulk analysis. For this reason, flow cytometry has been an effective tool for single-cell analysis of properties using light scattering and fluorescence labeling. However, conventional flow cytometry cannot measure cell mechanical properties, alterations of which contribute to the pathophysiology of hematologic diseases such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
243
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(249 citation statements)
references
References 64 publications
5
243
1
Order By: Relevance
“…Rosenbluth et al, proposed a microfluidic-based flow cytometer to measure the transit time of HL60 cells stimulated with Cytochalasin D and Pentoxifylline. They observed that median transit time was reduced from 0.63 s to 0.23 s for 1 h exposure of 2 μM of CytoD solution and to 0.37 s for 3 h exposure of 1 mM PTX solution (Rosenbluth et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosenbluth et al, proposed a microfluidic-based flow cytometer to measure the transit time of HL60 cells stimulated with Cytochalasin D and Pentoxifylline. They observed that median transit time was reduced from 0.63 s to 0.23 s for 1 h exposure of 2 μM of CytoD solution and to 0.37 s for 3 h exposure of 1 mM PTX solution (Rosenbluth et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs used for vascular complications can change biophysical properties of blood cells, due to their effect on cell membrane, cell cytoskeleton and cell fate, such as apoptosis (Lam et al 2007;Ruef et al 2010;Rosenbluth et al 2008;Wuang et al 2011;Dai et al 2010). Therefore, it is of significant importance to study mechano-biological changes of diseased circulating cells in the development of a new treatment.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of high-speed imaging or electrical impedance measurements, constriction-channel devices are capable of achieving a higher throughput than most other deformability measurement approaches. Due to these merits, constriction channels have been used to measure the deformability of RBCs, 22,23,[39][40][41][42][43][44] leukocytes 45 and cancer cells. 46,47 Due to the human capillary-like environment and the physiological relevance of RBC deformability, RBCs are mostly studied in the majority of existing constriction channel-based devices.…”
Section: Structure-induced Deformation (Constriction Channels)mentioning
confidence: 99%
“…Rosenbluth et al demonstrated the clinical relevance of their microfluidic constriction channel device in sepsis and leukostasis. 45 The reported device consists of a network of 64 constriction channels. High-speed imaging was used for measuring cell transit time.…”
Section: Structure-induced Deformation (Constriction Channels)mentioning
confidence: 99%
“…One approach is the microfluidic cell deformability cytometer which are inexpensive to prototype, use small sample volumes (nanoliters), and employ laminar flow characteristics (24) allowing for predictable and controllable flow. For example, physical constrictions (25)(26)(27)(28) or inertial focusing flow (29)(30)(31) have been used to create contact or shear forces (> 1 nN (30)) capable of significantly deforming flowing cells. Large strains (>10% deformation) however, can damage cells and should be avoided when cell isolation and viability post-analysis are of interest.…”
Section: Introductionmentioning
confidence: 99%